'Somewhere in blood soaked France' : the diary of Corporal Angus Mackay, Royal Scots, Machine Gun Corps., 1914-1917 /: the diary of Corporal Angus Mackay, Royal Scots, Machine Gun Corps., 1914-1917. (2011) - Unknown
No abstract available